Infrared induced reactivity on the surface of isolated size-selected clusters: dissociation of N2O on rhodium clusters. - Hamilton, S; Hopkins, W; Harding, D; Walsh, T; Gruene, P; Haertelt, M; Fielicke, A; Meijer, G; Mackenzie, S (2010)
Multiple photon infrared excitation of size-selected Rh(6)N(2)O(+) clusters drives surface chemistry resulting in partially oxidized clusters.